2014
DOI: 10.1002/ajpa.22687
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the spheno‐occipital synchondrosis in a modern Queensland, Australian population using computed tomography

Abstract: Due to disparity regarding the age at which skeletal maturation of the spheno-occipital synchondrosis occurs in forensic and biological literature, this study provides recalibrated multislice computed tomography (MSCT) age standards for the Australian (Queensland) population, using a Bayesian statistical approach. The sample comprises retrospective cranial/cervical MSCT scans obtained from 448 males and 416 females aged birth to 20 years from the Skeletal Biology and Forensic Anthropology Research Osteological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 48 publications
2
51
0
3
Order By: Relevance
“…Our results report older ages of fusion than reported by Flecker () in a similar Australian population, however it is not possible to determine whether this difference is due to differences in the imaging technology used where computed tomography allows a higher degree of accuracy in discriminating active fusion from complete fusion compared to plain radiography, whether the difference is due to secular change in maturation, and/or whether the difference is due to geographic population differences possibly due to variance in socioeconomic status between the States of Australia. Comparison of radiographic studies have suggested that fusion can be detected earlier and later in computed tomography compared to plain radiography (Langley‐Shirley and Jantz, ; Lottering et al, ) and Jantz et al () demonstrate significant changes in bone length and proportion in the long bones of American whites between 1840 and 1989 demonstrating the impact of secular change on skeletal development. Therefore, comparison of fusion times from studies using different imaging modalities, and on children of significantly different generational origins is cautioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results report older ages of fusion than reported by Flecker () in a similar Australian population, however it is not possible to determine whether this difference is due to differences in the imaging technology used where computed tomography allows a higher degree of accuracy in discriminating active fusion from complete fusion compared to plain radiography, whether the difference is due to secular change in maturation, and/or whether the difference is due to geographic population differences possibly due to variance in socioeconomic status between the States of Australia. Comparison of radiographic studies have suggested that fusion can be detected earlier and later in computed tomography compared to plain radiography (Langley‐Shirley and Jantz, ; Lottering et al, ) and Jantz et al () demonstrate significant changes in bone length and proportion in the long bones of American whites between 1840 and 1989 demonstrating the impact of secular change on skeletal development. Therefore, comparison of fusion times from studies using different imaging modalities, and on children of significantly different generational origins is cautioned.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comparison of fusion times from studies using different imaging modalities, and on children of significantly different generational origins is cautioned. Lottering et al () recommend that independent reference standards be available for each Australian State, with evidence of intrapopulation variation in the timing of fusion of the spheno‐occipital synchondrosis between Queensland, Western Australian (Franklin and Flavel, ) and Victorian (Bassed et al, ) studies. Queensland children demonstrated earlier fusion of the spheno‐occipital synchondrosis compared to their Australian interstate counterparts by 1–2 years (Lottering et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The basilar process meets with the body of the sphenoid at the spheno-occipital synchondrosisan important postnatal growth area (Moore and Lavelle, 1974;Sperber, 1989;Scheuer and Black, 2004;Standring and Gray, 2008;Lottering et al, 2015).…”
Section: Basilar Processmentioning
confidence: 99%
“…Though the mid-sphenoidal synchondrosis remains active later in non-human primates, this synchondrosis closes before birth in humans (Ford, 1958;Scott, 1958;Michejda, 1971;Lieberman et al, 2008). The sphenooccipital synchondrosis is the last of the three synchondroses to fuse in human development, with growth at this site continuing into adolescence (Björk, 1955;Scott, 1958;Lieberman et al, 2000b;Lottering et al, 2015). This synchondrosis has been argued to play a major role in postnatal cranial base flexion (Lieberman, 2000;Lieberman et al, 2000b;.…”
Section: Ontogeny Of Cranial Base Flexionmentioning
confidence: 99%
See 1 more Smart Citation